Carrier induced degradation in compensated n-type silicon solar cells: Impact of light-intensity, forward bias voltage, and temperature on the reaction kinetics. (24th July 2017) - Shen, Daniel; Sun, Chang; Zheng, Peiting; Macdonald, Daniel; Rougieux, Fiacre
Abstract: We analyze the formation kinetics of the boron–oxygen defect in compensated n-type upgraded metallurgical-grade (UMG) silicon solar cells. Through time-resolved open-circuit voltage measurements, we explore the influence of temperature, forward bias, and light intensity on the formation kinetics of the defect. Our results confirm that the boron–oxygen defect forms more slowly in compensated n-type silicon than in p-type silicon. We present evidence which suggests that the slower kinetics in n-type silicon may be due to a lower frequency factor for defect formation.